Polyether organic silicon composite material and method for preparing synthetic leather from polyether organic silicon composite material
By using a polyether silicone combination based on silanoxy-terminated polyether and polyorganosiloxane, the problem of poor mechanical properties of existing silicone leather is solved through the polycondensation reaction under the action of water vapor, and strength improvement and multiple performance optimization are achieved.
Patent Information
- Application Number
- CN202411768182.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-11
AI Technical Summary
The existing commercially available silicone leather has poor mechanical properties and strength, and there are few other preparation methods except for the hydrosilicification addition method.
Polyether silicone synthetic leather is prepared by bonding polyether ended polyether, α,ω-bis(siloxane)-terminated polyorganosiloxane, and single-ended polyorganosiloxane with siloxane-terminated polyether was prepared by bonding and polycondensation under the action of water vapor.
The mechanical properties and strength of silicone leather have been improved, especially in terms of tear resistance and fracture strength, while maintaining good water repellency, dust resistance, aging resistance and easy-to-maintenance.
Smart Images

Figure BDA0005169537860000021 
Figure BDA0005169537860000031 
Figure BDA0005169537860000041
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of functional materials and modified silicone leather, and specifically relates to a polyether silicone composite material obtained based on silaneoxy-terminated polyether and silaneoxy-terminated urethane-based (polyether-based) polyorganosiloxane, natural leather collagen powder, etc., and a method for preparing silicone leather based on the composite material. Background Art
[0002] Silicone leather, that is, artificial leather made from silicone rubber, is not only famous for its weather resistance, aging resistance, waterproof, dustproof, anti-fouling, and easy cleaning, but also has a wide range of applications in many fields such as automotive interior leather, sports shoe leather, luggage leather, interior decoration materials, and electronic product accessories (such as sports bracelets, iPads, and mobile phone cases). Therefore, it has become a research and development hotspot in the fields of silicone, leather, and new functional materials in recent years, and a product that many manufacturers are competing to develop (see CN117779479A, CN 115652651A, CN117487456A, CN115595800A, etc.).
[0003] However, from the literature and market research, it can be seen that the silicone leather currently on the market is mainly silicone leather produced by hydrogenated addition reaction of hydrogenated silicone oil, vinyl silicone rubber, fumed silica, etc. In addition, there are few research reports on the production of silicone leather by other methods. In addition, compared with natural leather, it can be seen that the mechanical properties and strength (such as tear resistance and breaking strength) of the addition-type silicone leather currently on the market are poor due to the good hydrophobicity of the polydimethylsiloxane segment of the silicone rubber main chain and the weak interaction between the hydrophobic chains, which needs to be improved.
[0004] As is known to all, alkoxysilanes have strong adhesion to substrates and are easily hydrolyzed and polycondensed under the action of water or moisture in the air to form elastomers. In addition, the introduction of phenyl groups into the polysiloxane structure can improve the miscibility of polysiloxanes with aliphatic organic resins. Based on this, polyethers with 2-3 functional silane alkoxy end groups and polysiloxanes with 2-3 functional silane alkoxy end groups are bonded and polycondensed under the action of water vapor to obtain polyether hybrid silicone cross-linked elastomers. However, there are no reports in the literature on whether polyether silicone leather can be prepared by this hydrolysis and polycondensation method. Summary of the invention
[0005] In view of the defects of commercially available organosilicon leather and the fact that there are few preparation methods other than the hydrosilylation addition method, the present invention discloses a polyether organosilicon composite material prepared based on α,ω-silanoxy-terminated polyether, α,ω-bis(siloxane)-terminated polyorganosiloxane, and polyorganosiloxane with a single end terminated by siloxane, and a method for preparing polyether organosilicon synthetic leather by polycondensation using the composite material. To this end, the present invention adopts the following technical scheme:
[0006] A polyether silicone composite material comprises the following components in parts by mass: 60-90 parts of α,ω-bis(siloxy)-terminated polyether (MS glue), 5-30 parts of α,ω-bis(siloxy)-terminated polyorganosiloxane (DPS), 5-10 parts of single-end (siloxy)-terminated polyorganosiloxane, 0.5-10 parts of oil-soluble color paste, 0.5-1.0g of wetting dispersant, 10-25 parts of skin collagen powder, 10-30 parts of alcohol-water solvent, 0.2-0.5 parts of organic metal catalyst, etc. The components are stirred, dispersed and mixed evenly, and then vacuumed and degassed to obtain a uniform fluid, which is the polyether silicone composite material.
[0007] The α,ω-bis(siloxy) terminated polyether (MS glue) is a polyether with a 2-3 functional siloxy group connected to each end of the molecule, also known as bis(2-3 functional siloxy) terminated polyether, with a viscosity of 5000-20000mPa.s, purchased from Shanghai Dongda Chemical Co., Ltd. or Zhangjiagang Top Chemical Co., Ltd.; the polyether in the MS glue is generally a polyoxypropylene ether group, and the alkoxy group is a methoxy group or an ethoxy group.
[0008] The α,ω-bis(siloxy)-terminated polyorganosiloxane (DPS) has a structure as shown in formula (1), which is an organosilicon polymer with a 2-3 functional siloxy group (i.e., 2-3 reactive Si-OR) connected to each end of the molecule and a carbamate (polyether) block polyorganosiloxane in the middle, also known as α,ω-bis(siloxy)-terminated carbamate (polyether) block polyorganosiloxane. In formula (1), n1, n2 = 0-40, n1+n2 = 4-40, R = CH3 or C2H5, R1, R2, R3, R4 = CH3 or C6H5 (abbreviated as ph), R1 to R4 can be the same or different; A = -(OC2H4) a (OC3H6) b -, a=0-3, b=0-10, a+b=0-10; x=1-2;
[0009]
[0010] The polyorganosiloxane main chain in the DPS is generally one of polydimethylsiloxane, polydiphenylsiloxane, polymethylphenylsiloxane, poly(dimethylsiloxane-co-diphenylsiloxane), and poly(dimethylsiloxane-co-methylphenylsiloxane); the polyether group is a polyoxyethylene polyoxypropylene ether group with a=0-3, b=0-10, and a+b=0-10.
[0011] The α,ω-bis(siloxy)-terminated urethane (polyether) block polyorganosiloxane (DPS) can be prepared by reacting a (polyether) block polyorganosiloxane (HO-PS-OH) having C-OH groups at both ends of the molecule as shown in formula (2) with a 3-isocyanate silane (ICS) having 2-3 alkoxy groups in the structure; in the reaction, the molar ratio of HO-PS-OH to ICS is about 1:2-5, the reaction temperature is 50-80°C, the reaction time is about 4-6h, and after the reaction is completed, the target product DPS can be obtained by decompressing and removing the low boiling point; in formula (2), the definitions and values of n1, n2, R1, R2, R3, R4, A, a, and b are the same as those in formula (1).
[0012]
[0013] The (polyether) block polyorganosiloxane [HO-PS-OH, formula (2)] containing C-OH at both ends of the molecule, the definitions of the polyether group and the polyorganosiloxane main chain are the same as those of formula (1), and the selected ones are α,ω-bis(hydroxypropyl) block polydimethylsiloxane, α,ω-bis(hydroxypropyl) block polydiphenylsiloxane, α,ω-bis(hydroxypropyl) block polymethylphenylsiloxane, α,ω-bis(hydroxypropyl) block poly(dimethylsiloxane-co-diphenylsiloxane), α,ω-bis(hydroxypropyl) block poly(dimethylsiloxane-co-methylphenylsiloxane) , α,ω-bis(hydroxyethyloxypropyl) block polydimethylsiloxane, α,ω-bis(hydroxyethyloxypropyl) block polydiphenylsiloxane, α,ω-bis(hydroxyethyloxypropyl) block polymethylphenylsiloxane, α,ω-bis(hydroxyethyloxypropyl) block poly(dimethylsiloxane-co-diphenylsiloxane), α,ω-bis(hydroxyethyloxypropyl) block poly(dimethylsiloxane-co-methylphenylsiloxane), a=0-3, b=0-10, a+b=0-10 α,ω-bis(hydroxy-terminated polyoxyethylene polyoxypropylene propyl) block polydimethylsiloxane Methylsiloxane, α,ω-bis(hydroxy-terminated polyoxyethylene polyoxypropylene propyl) block polydiphenylsiloxane, a=0-3, b=0-10, a+b=0-10, α,ω-bis(hydroxy-terminated polyoxyethylene polyoxypropylene propyl) block polymethylphenylsiloxane, a=0-3, b=0-10, a+b=0-10, α,ω-bis(hydroxy-terminated polyoxyethylene polyoxypropylene propyl) block poly(dimethylsiloxane-co-diphenylsiloxane), a=0-3, b=0-10, a+b=0-10 0, a+b=0-10 one of α,ω-bis(hydroxy-terminated polyoxyethylene polyoxypropylene propyl) block poly(dimethylsiloxane-co-methylphenylsiloxane); the (polyether) block polyorganosiloxane (HO-PS-OH) containing C-OH at both ends of the molecule can be prepared by the hydrosilylation addition reaction of the hydrogen-containing polyorganosiloxane at both ends of the molecule blocked with dimethyl hydrogen silicon with allyl alcohol, hydroxyethyl allyl ether, and hydroxy-terminated polyoxyethylene polyoxypropylene allyl ether, and can be ordered from Zhejiang Runhe New Materials Co., Ltd., Anhui Aiyota Silicone Co., Ltd. and other units.
[0014] The 3-isocyanate silane (ICS) is selected from one of 3-isocyanate propyl trimethoxy silane (ICPTMS), 3-isocyanate propyl triethoxy silane (ICPTES), 3-isocyanate propyl methyl dimethoxy silane (ICPMDMS), and 3-isocyanate propyl methyl diethoxy silane (ICPMDES).
[0015] The single-end silaneoxy terminated polyorganosiloxane (MPS) has a structure as shown in formula (3), which is a carbamate (polyether) polyorganosiloxane having a 2-3 functional silaneoxy group at one end of the molecule and a trimethylsilyl terminated carbamate (polyether) polyorganosiloxane at the other end, also known as a single-end silaneoxy terminated carbamate (polyether) polyorganosiloxane. In formula (3), m1, m2 = 0-40, m1 + m2 = 4-40, R1', R2', R3', R4' = CH3 or C6H5, R1' to R4' can be the same or different; A' = -(OC2H4) a1 (OC3H6) b1 -, a1 = 0-3, b1 = 0-10, a1 + b1 = 0-10; R' = CH3 or C2H5, y = 1 or 2;
[0016]
[0017] The polyorganosiloxane main chain in the MPS can be one of monotrimethylsilyl-terminated polydimethylsiloxane, monotrimethylsilyl-terminated polydiphenylsiloxane, monotrimethylsilyl-terminated polymethylphenylsiloxane, monotrimethylsilyl-terminated poly(dimethylsiloxane-co-diphenylsiloxane), and monotrimethylsilyl-terminated poly(dimethylsiloxane-co-methyldiphenylsiloxane), and the polyether group is a polyoxyethylene polyoxypropylene group with a1=0-3, b1=0-10, and a1+b1=0-10.
[0018] The single-end silaneoxy-terminated polyorganosiloxane (MPS) is synthesized in a similar manner to the α,ω-bis(alkoxysilyl)-terminated carbamate-based (polyether) polyorganosiloxane, and can also be prepared by chemically reacting a single-end C-OH-containing (polyether-based) polyorganosiloxane PS-OH [see formula (4), m1, m2, R1', R2', R3', R4', A', a1, b1, etc. are all the same as formula (3)] with isocyanate silane (ICS); the PS-OH reacts with ICS, the molar ratio of PS-OH:ICS is still 1:1-5, and the reaction temperature and reaction time are the same as before.
[0019]
[0020] The (polyether) polyorganosiloxane (PS-OH) having a C-OH group at one end of the molecule shown in formula (4), the definitions of the polyether group and the main chain polyorganosiloxane are the same as those of formula (3), and the selected ones are monohydroxypropyl polydimethylsiloxane, monohydroxypropyl polydiphenylsiloxane, monohydroxypropyl polymethylphenylsiloxane, monohydroxypropyl poly(dimethylsiloxane-co-diphenylsiloxane), monohydroxypropyl poly(dimethylsiloxane-co-methylphenylsiloxane), monohydroxyethyloxypropyl Polydimethylsiloxane, monohydroxyethyloxypropyl polydiphenylsiloxane, monohydroxyethyloxypropyl polymethylphenylsiloxane, monohydroxyethyloxypropyl poly(dimethylsiloxane-co-diphenylsiloxane), monohydroxyethyloxypropyl poly(dimethylsiloxane-co-methylphenylsiloxane), monohydroxyethyloxypropyl poly(dimethylsiloxane-co-methylphenylsiloxane), monohydroxyethyloxypropyl poly(dimethylsiloxane-co-methylphenylsiloxane), monohydroxy-terminated polyoxyethylene polyoxypropylene propyl polydimethylsiloxane with a1=0-3, b1=0-10, a1+b1=0-10, a1=0-3, b1=0 -10, a1+b1=0-10 monohydroxy-terminated polyoxyethylene polyoxypropylene propyl polydiphenylsiloxane, a1=0-3, b1=0-10, a1+b1=0-10 monohydroxy-terminated polyoxyethylene polyoxypropylene propyl polymethylphenylsiloxane, a1=0-3, b1=0-10, a1+b1=0-10 monohydroxy-terminated polyoxyethylene polyoxypropylene propyl poly(dimethylsiloxane-co-diphenylsiloxane), a1=0 -3, b1=0-10, a1+b1=0-10, one of the monohydroxy-terminated polyoxyethylene polyoxypropylene propyl poly(dimethylsiloxane-co-methylphenylsiloxane), which can be prepared by the hydrosilylation addition reaction of single-end dimethyl hydrogen silicon-terminated polyorganosiloxane with allyl alcohol, hydroxyethyl allyl ether, and hydroxy-terminated polyoxyethylene polyoxypropylene allyl ether, and can be ordered from Zhejiang Runhe New Materials Co., Ltd., Anhui Aiyota Silicone Co., Ltd. and other units.
[0021] The color paste is a dispersion formed by oil-soluble dyes or pigments dispersed in resins or solvents, and is selected from the Swiss Clariant black color paste Colanyl Black N131-CN 0030, or the solvent-based resin universal color paste produced by Henan Wangong Environmental Protection Materials Co., Ltd., such as DF616 Permanent Red F5, DF618 Permanent Red F2, DF816 Standard Yellow, etc.; the wetting and dispersing agent is one of BYK-ATU, BYK-163, etc. used in the oil-soluble system produced by German BYK.
[0022] The skin collagen powder (also known as skin collagen fiber powder) is a powdery substance obtained by recycling, decolorizing and crushing the scraps produced in the processing and production process of natural leather such as pig skin, cow skin and sheep skin.
[0023] The alcohol-water solvent is an alcohol-water mixture (abbreviated as 90%-95% alcohol) in which 5%-10% water is dissolved in a small molecule alcohol. The small molecule alcohol is one of ethanol, isopropanol, tert-butanol, etc., and its content is about 90%-95% of the mass of the alcohol-water mixture.
[0024] The organic metal catalyst is a catalyst capable of catalyzing the hydrolysis and polycondensation reaction of silaneoxy (Si-OR), and is selected from one of dibutyltin dilaurate, dibutyltin diacetate, bismuth diisooctanoate, zinc diisooctanoate and the like.
[0025] The method for preparing synthetic leather from a polyether silicone composite material comprises the following specific preparation steps:
[0026] Take the substrate base and fix it on the test bench, first apply a layer of primer resin prepared by aminosilane ring-opening modified epoxy resin (AE) on the surface of the substrate with a wire rod, a coating instrument or a scraper, and then evenly apply the polyether silicone combination material on the surface of the substrate that has been primer-treated, and control the coating amount so that the coating thickness formed after the polyether silicone combination material is cured is about 150-300μm, and then paste a layer of fluorine texture release paper, and then cure at room temperature for 24-48h, remove the release paper, and then spray a leather feel agent-ethanol solution with a mass concentration of about 0.5% on the leather surface, dry it, and the resulting leather sample is the synthetic leather prepared by the polyether silicone combination material.
[0027] The base material base is one of non-woven fabrics made of polyester, nylon and spandex (polyurethane), or ultra-fine fiber fabrics.
[0028] The aminosilane ring-opening modified epoxy resin is a product obtained by reacting bisphenol A epoxy resin and monoamine aminosilane at a ratio of about 1:2-2.3 at 50-70°C for 30-60 minutes; the epoxy resin is bisphenol A epoxy resin E51 or E44, and the monoamine aminosilane is one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane (KH-550), 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, etc.
[0029] The leather feel agent is a substance sprayed on the surface of leather or synthetic leather to produce a smooth and moist feeling or a sheepskin-like oily and moist feeling. The leather feel agent DC-Q2-3238 produced by Dow Corning Company of the United States or one of similar products is selected.
[0030] The beneficial effects of the present invention are as follows: based on the characteristics that silaneoxy groups are easily hydrolyzed to generate Si-OH under the action of water vapor or moisture in the air, and Si-OH is easily dealcoholized or de-H2O cross-linked with Si-OR or Si-OH, the present invention uses a newly designed and synthesized carbamate (polyether) polyorganosiloxane DPS with 2-3 functional silaneoxy groups at both ends of the molecule and Si-CH3 and Si-ph in the main chain, a carbamate (polyether) polyorganosiloxane MPS with one 2-3 functional silaneoxy group at one end of the molecule, and a double (silaneoxy)-terminated polyether MS as reactive resin components, and skin collagen powder as a moisture-absorbing and breathable filler component. Under the action of coating additives, the components are compounded to form a polyether silicone composite material, and then the composite material is coated on the surface of an ultrafine fiber base cloth or a non-woven fabric substrate, and the resin end groups are cross-linked and cured by using moisture in the air or trace moisture in the system, thereby preparing a polyether silicone composite material. Silicone synthetic leather; in addition, the present invention introduces silane alkoxy and polyether groups into the low surface energy oligosiloxane structure by molecular design. Based on the similar compatibility of groups and segment structures, the silicone composite material made of MS, DPS, MPS, etc. in the present invention can achieve mutual solubility without phase separation, and can also obtain synthetic leather with surface energy showing silicone rubber characteristics and internal curing similar to MS coating by one-step curing through the tendency of high surface energy polyether segments to the bottom and low surface energy polysiloxane segments to the surface during curing, especially by utilizing the characteristics of single-end polysiloxane that is easy to migrate out of the coating surface; applications show that the silicone synthetic leather prepared in this way by the present invention, after being modified with a leather feel agent, can not only produce a comfortable, moisturizing and oily feeling similar to natural leather on the surface, as well as good water repellency, dustproofness, aging resistance and easy care properties similar to silicone leather, but also the inner layer of the leather can also have good elongation at break and mechanical strength generated by the MS cross-linked segments. DETAILED DESCRIPTION
[0031] The present invention will be further described below in conjunction with embodiments, but the present invention is not limited to the embodiments.
[0032] Example 1
[0033] (1) Preparation of relevant raw materials
[0034] 1) Synthesis of bis(siloxy)-terminated carbamate-based polyether-based polyorganosiloxane (DPS-1)
[0035] In a dry three-necked flask equipped with a thermometer, a reflux condenser and an electric stirrer, 0.01 mol (63.86 g) of α,ω-bis(hydroxy-terminated polyoxypropylenepropyl) block polymethylphenylsiloxane HO(C3H6O)6C3H6Si(CH3)2[OSi(CH3)ph] having a structure shown in formula (2) with n1=0, n2=40, R3=CH3, R4=ph, a=0, b=6, A=-(OC3H6)6- was weighed in a molar ratio of about 1:3 between polyether polyorganosiloxane (HO-PS-OH) containing C-OH at both ends of the molecule and isocyanate silane (ICS). 40 OSi(CH3)2C3H6(OC3H6)6OH and 0.03 mol (about 6.16 g) 3-isocyanatepropyltrimethoxysilane (ICPTMS) were stirred and mixed, and the mixture was heated to 50°C and stirred for 4 hours. After the reaction was completed, 表 =0.09MPa, the residual 3-isocyanatepropyltrimethoxysilane was evaporated under reduced pressure to obtain a colorless transparent liquid, i.e., α,ω-bis(trimethoxysilylpropylcarbamate-based polyoxypropylenepropyl) block polymethylphenylsiloxane having a structure as shown in formula (1), wherein n1=0, n2=40, R3=CH3, R4=ph, a=0, b=6, A=-(OC3H6)6-, R=CH3, and x=1, denoted as DPS-1.
[0036] 2) Synthesis of single-end silaneoxy terminated urethane polyether polyorganosiloxane (MPS-1)
[0037] In a dry three-necked flask equipped with a thermometer, a reflux condenser and an electric stirrer, 0.01 mol (33.34 g) of a single-ended (hydroxy-terminated polyoxypropylene propyl) polydimethylsiloxane (CH3)3Si[OSi(CH3)2] having a structure shown in formula (4) with m1=40, m2=0, R1'=R2'=CH3, a1=0, b1=3, A'=-(OC3H6)3- was weighed in a molar ratio of about 1:2.5 between polyether-based polyorganosiloxane (PS-OH) containing C-OH at one end of the molecule and isocyanate-based silane (ICS). 40 OSi(CH3)2C3H6(C3H6O)3OH and 0.025mol (5.13g) 3-isocyanatepropyltrimethoxysilane (ICPTMS) were stirred and mixed, and heated to 50°C and stirred for 4h. After the reaction was completed, 表=0.09MPa, the residual ICPTMS was evaporated under reduced pressure to obtain a colorless transparent liquid, which is a single-terminal (trimethoxysilylpropylcarbamate polyoxypropylenepropyl) polydimethylsiloxane having a structure as shown in formula (3) with m1=40, m2=0, R1'=R2'=CH3, a1=0, b1=3, A'=-(OC3H6)3-, y=1, and R'=CH3, denoted as MPS-1, and used for later use.
[0038] (2) Preparation of polyether silicone composite material SMS-1
[0039] 60.0 g of α, ω-bis(methyldimethoxysilyl) end-capped polyether S316 (Shanghai Dongda Chemical Co., Ltd.) with a viscosity of about 8000 mPa.s, 30.0 g of α, ω-bis(trimethoxysilylpropylcarbamate-polyoxypropylenepropyl) block polymethylphenylsiloxane DPS-1, 10.0 g of single-end (trimethoxysilylpropylcarbamate-polyoxypropylenepropyl) polydimethylsiloxane MPS-1, 1.0 g of Clariant oil-soluble black color paste Colanyl Black N131-CN0030, 0.5 g of BYK-ATU dispersant, and 10.0 g of skin collagen powder were weighed in order by mass, and the mixture was stirred and mixed with a dispersion disk at a speed of 1000 r / min, and then 10.0 g of 95% ethanol solvent was added and continued to stir and disperse for 30 min, and vacuum degassing was performed, and then 0.5 g of dibutyltin dilaurate and 1.0 g of KH-550 catalyst is stirred and mixed, and the resulting slurry is a polyether silicone composite material, recorded as SMS-1.
[0040] (3) Preparation of polyether silicone leather PESiL-1
[0041] S1: Take 0.2mol (about 44.27g) of 3-aminopropyltriethoxysilane KH-550, 0.1mol (about 45.45g) of epoxy resin E44, and 90.0g of propylene glycol dimethyl ether (DMP) solvent, stir and mix, heat to 60°C and stir to react for 60min, and obtain a transparent liquid, which is the base adhesive AE-1; take a polyester microfiber base cloth (referred to as super fiber, Changshu Jinda Nonwoven Products Co., Ltd.) and fix it on the test bench, use a 25μm wire rod to evenly apply AE-1 on the surface of the polyester microfiber base cloth, and then bake it at 100°C for 10min to obtain the base cloth treated with the base adhesive AE-1;
[0042] S2: Take the polyether silicone combination material SMS-1, and use an RDS-70 wire rod to evenly coat the SMS-1 on the surface of the base fabric treated with AE-1 obtained in step S1, and control the coating amount so that the coating thickness formed after the polyether silicone combination material is cured is about 180μm, and then stick a layer of fluorine texture release paper, and then cure it at room temperature for 24h. After the surface is completely cured, remove the release paper, and then spray the newly exposed leather surface with a leather feel agent DC-Q2-3238-ethanol solution with a mass concentration of about 0.5%, and hang it in a drying room at 90℃ for 1h. The resulting leather sample is the polyether silicone synthetic leather PESiL-1.
[0043] Example 2
[0044] (1) Preparation of relevant raw materials
[0045] 1) Synthesis of bis(siloxy)-terminated urethane polyether polyorganosiloxane (DPS-2)
[0046] In a dry three-necked flask equipped with a thermometer, a reflux condenser and an electric stirrer, 0.01 mol (about 25.78 g) of α,ω-bis(hydroxy-terminated polyoxypropylenepropyl) block polydiphenylsiloxane HO(C3H6O)3C3H6Si(CH3)2[OSi(C6H5)2] having a structure shown in formula (2) with n1=0, n2=10, R3=R4=ph, a=0, b=3, A=-(OC3H6)3- was weighed at a molar ratio of about 1:2.2 between polyether polyorganosiloxane (HO-PS-OH) containing C-OH at both ends of the molecule and isocyanate silane (ICS). 10 OSi(CH3)2C3H6(OC3H6)3OH and 0.022 mol (about 4.52 g) 3-isocyanatepropyltrimethoxysilane (ICPTMS) were stirred and mixed, and the mixture was heated to 80°C and stirred for 6 hours. After the reaction was completed, 表 =0.09MPa, the residual 3-isocyanatepropyltrimethoxysilane was evaporated under reduced pressure to obtain a colorless transparent liquid, i.e., α,ω-bis(trimethoxysilylpropylcarbamate-based polyoxypropylenepropyl)polydiphenylsiloxane having a structure as shown in formula (1), wherein n1=0, n2=10, R3=R4=ph, a=0, b=3, A=-(OC3H6)3-, R=CH3, and x=1, denoted as DPS-2.
[0047] 2) Synthesis of single-end silaneoxy terminated urethane polyether polyorganosiloxane (MPS-2)
[0048] In a dry three-necked flask equipped with a thermometer, a reflux condenser and an electric stirrer, 0.01 mol (about 59.36 g) of a single-ended (hydroxy-terminated polyoxypropylene propyl) poly(dimethylsiloxane-co-diphenylsiloxane) (CH3)3Si[OSi(CH3)2] having a structure shown in formula (4) with m1=20, m2=20, R1'=R2'=CH3, R3'=R4'=ph, a1=0, b1=5, A'=-(OC3H6)5- was weighed in a molar ratio of about 1:3 between polyether-based polyorganosiloxane (PS-OH) containing C-OH at one end of the molecule and isocyanate-based silane (ICS). 20 [OSi(C6H5)2] 20 OSi(CH3)2C3H6(OC3H6)5OH and 0.03 mol (about 6.15 g) 3-isocyanatepropyltrimethoxysilane (ICPTMS) were stirred and mixed, and heated to 50°C and stirred for 6 hours. After the reaction was completed, 表 =0.09MPa, and the residual ICPTMS was evaporated under reduced pressure to obtain a colorless transparent liquid, which is a single-terminal (trimethoxysilylpropylcarbamate polyoxypropylenepropyl) poly(dimethylsiloxane-co-diphenylsiloxane) having a structure as shown in formula (3) with m1=20, m2=20, R1'=R2'=CH3, R3'=R4'=ph, a1=0, b1=5, A'=-(OC3H6)5-, y=1, and R'=CH3, denoted as MPS-2, for future use.
[0049] (2) Preparation of polyether silicone composite material SMS-2
[0050] 80.0 g of α, ω-bis(methyldimethoxysilyl) end-capped polyether S312 (Shanghai Dongda Chemical Co., Ltd.) with a viscosity of about 12000 mPa.s, 10.0 g of α, ω-bis(trimethoxysilylpropylcarbamate polyoxypropylenepropyl) polymethylphenylsiloxane DPS-2, 10.0 g of single-ended (trimethoxysilylpropylcarbamate polyoxypropylenepropyl) poly(dimethylsiloxane-co-diphenylsiloxane) MPS-2, 1.0 g of Clariant oil-soluble black color paste ColanylBlack N131-CN0030, 0.5 g of BYK-ATU dispersant, and 20.0 g of skin collagen powder were weighed in parts by mass, stirred and mixed with a dispersing disk at a speed of 1000 r / min, and then 20.0 g of The 90% ethanol solvent was stirred and dispersed for 60 minutes, and vacuum was used for degassing. Then, 0.5 g of bismuth diisooctanoate and 1.0 g of KH-550 catalyst were added and stirred to mix well. The obtained slurry was a polyether silicone composite material, which was recorded as SMS-2.
[0051] (3) Preparation of polyether silicone synthetic leather PESiL-2
[0052] S1: The base fabric treated with base adhesive AE-1 is the same as that in Example 1.
[0053] S2: Take the polyether silicone combination material SMS-2, and use RDS-70 wire rod to evenly coat SMS-2 on the surface of the polyester microfiber base fabric that has been treated with AE-1 primer, and control the coating amount so that the coating thickness formed after the polyether silicone combination material is cured is about 230μm, and then stick a layer of fluorine texture release paper, and then cure at room temperature for 48h. After the surface is completely cured, remove the release paper, and then spray the newly exposed leather surface with a leather feel agent DC-Q2-3238-ethanol solution with a mass concentration of about 0.5%, and hang it in a drying room at 80℃ for 1h. The resulting leather sample is the polyether silicone synthetic leather PESiL-2.
[0054] Example 3
[0055] (1) Preparation of relevant raw materials
[0056] 1) Synthesis of bis(siloxy)-terminated urethane polyether polyorganosiloxane (DPS-3)
[0057] In a dry three-necked flask equipped with a thermometer, a reflux condenser and an electric stirrer, 0.01 mol (about 54.44 g) of a polyether polysiloxane (HO-PS-OH) containing C-OH at both ends of the molecule and 3-isocyanate silane (ICS) were weighed in a molar ratio of about 1:4. The structure is shown in formula (2): n1 = 10, n2 = 20, R1 = R2 = CH3, R3 = R4 = ph, a = 0, b = 10, A = -(OC3H6) 10 α,ω-bis(hydroxy-terminated polyoxypropylene propyl) block poly(dimethylsiloxane-co-diphenylsiloxane) HO(C3H6O) 10 C3H6Si(CH3)2[OSi(CH3)2] 10 [OSi(C6H5)2] 20 OSi(CH3)2C3H6(OC3H6) 10 OH and 0.04 mol (about 9.89 g) 3-isocyanate propyl triethoxysilane (ICPTES), stir and mix, heat to 70 ° C and stir for 4 h; after the reaction is completed, 表 =0.09MPa under reduced pressure to remove the residual 3-isocyanatepropyltriethoxysilane to obtain a colorless transparent liquid, i.e., the structure is as shown in formula (1): n1=10, n2=20, R1=R2=CH3, R3=R4=ph, a=0, b=10, A=-(OC3H6) 10α,ω-bis(triethoxysilylpropylcarbamate polyoxypropylenepropyl) block poly(dimethylsiloxane-co-diphenylsiloxane), wherein R=C2H5 and x=1, is denoted as DPS-3.
[0058] 2) Synthesis of single-end silaneoxy terminated urethane polyether polyorganosiloxane (MPS-3)
[0059] In a dry three-necked flask equipped with a thermometer, a reflux condenser and an electric stirrer, 0.01 mol (about 55.32 g) of a single-ended (hydroxy-terminated polyoxypropylene propyl) polymethylphenylsiloxane (CH3)3Si[OSiCH3(C6H5)] having a structure shown in formula (4) with m1=38, m2=0, R1'=CH3, R2'=ph, a1=0, b1=3, A'=-(OC3H6)3- was weighed in a molar ratio of (polyether) polyorganosiloxane (PS-OH) containing C-OH at one end of the molecule to 3-isocyanate silane (ICS) of about 1:1.5. 38 OSi(CH3)2C3H6(OC3H6)3OH and 0.04 mol (about 7.57 g) 3-isocyanatepropylmethyldimethoxysilane (ICPMDMS) were stirred and mixed, and heated to 70°C and stirred for 6 hours. After the reaction was completed, 表 =0.09MPa, and the residual 3-isocyanatepropylmethyldimethoxysilane was evaporated under reduced pressure to obtain a colorless transparent liquid, which is a single-terminal (methyldimethoxysilylpropylcarbamate-based polyoxypropylenepropyl) polymethylphenylsiloxane having a structure as shown in formula (3) with m1=38, m2=0, R1'=CH3, R2'=ph, a1=0, b1=3, A'=-(OC3H6)3-, y=2, and R'=CH3, denoted as MPS-3, and used for later use.
[0060] (2) Preparation of polyether silicone composite material SMS-3
[0061] 80.0 g of α, ω-bis(methyldimethoxysilyl) end-capped polyether S230 (Shanghai Dongda Chemical Co., Ltd.) with a viscosity of about 5000 mPa.s, 25.0 g of α, ω-bis(triethoxysilylpropylcarbamate-polyoxypropylenepropyl) polymethylphenylsiloxane DPS-3, 5.0 g of single-ended (methyldimethoxysilylpropylcarbamate-polyoxypropylenepropyl) polymethylphenylsiloxane MPS-3, 1.0 g of Clariant oil-soluble black color paste Colanyl Black N131-CN0030, 0.8 g of BYK-ATU dispersant, and 15.0 g of skin collagen powder were weighed in parts by mass, and stirred with a dispersing disk at a speed of 1000 r / min, and then 15.0 g of The 90% ethanol solvent was stirred and dispersed for 50 minutes, and vacuum was used for degassing. Then, 0.5 g of zinc diisooctanoate and 1.0 g of KH-550 catalyst were added and stirred to mix well. The obtained slurry was a polyether silicone composite material, which was recorded as SMS-3.
[0062] (3) Preparation of polyether silicone leather PESiL-3
[0063] S1: The base fabric treated with base adhesive AE-1 is the same as that in Example 1.
[0064] S2: Take the polyether silicone combination material SMS-3, and use RDS-70 wire rod to evenly coat SMS-3 on the surface of the polyester microfiber base cloth treated with AE-1, and control the coating amount so that the coating thickness formed after the polyether silicone combination material is cured is about 205μm, and then stick a layer of fluorine texture release paper, and then cure it at room temperature for 24h. After the surface is completely cured, remove the release paper, and then spray the newly exposed leather surface with a leather feel agent DC-Q2-3238-ethanol solution with a mass concentration of about 0.5%, and hang it in a drying room at 90℃ for 45min. The resulting leather sample is the polyether silicone synthetic leather PESiL-3.
[0065] Example 4
[0066] (1) Preparation of relevant raw materials
[0067] 1) Synthesis of bis(siloxy)-terminated urethane polyether polyorganosiloxane (DPS-4)
[0068] In a dry three-necked flask equipped with a thermometer, a reflux condenser and an electric stirrer, 0.01 mol (about 34.38 g) of α,ω-bis(hydroxy-terminated polyoxypropylenepropyl)-block poly(dimethylsiloxane-co-methylphenylsiloxane) HO(C3H6O)3C3H6Si(CH3)2[OSi(CH3)2] having a structure shown in formula (2) with n1=20, n2=10, R1=R2=R3=CH3, R4=ph, a=0, b=3, A=-(OC3H6)3- was weighed in a molar ratio of about 1:3 between polyether polyorganosiloxane containing C-OH at both ends of the molecule (HO-PS-OH) and isocyanate silane (ICS). 20 [OSiCH3(C6H5)] 10 OSi(CH3)2C3H6(C3H6O)3OH and 0.03 mol (about 6.52 g) 3-isocyanatepropylmethyldiethoxysilane (ICPMDES) were stirred and mixed, and heated to 60°C and stirred for 4 hours. After the reaction was completed, 表 =0.09MPa, the residual 3-isocyanatepropylmethyldiethoxysilane was evaporated under reduced pressure to obtain a colorless transparent liquid, i.e., α,ω-bis(methyldiethoxysilylpropylcarbamate-based polyoxypropylenepropyl)poly(dimethylsiloxane-co-methylphenylsiloxane) having a structure as shown in formula (1), wherein n1=20, n2=10, R1=R2=R3=CH3, R4=ph, a=0, b=3, A=-(OC3H6)3-, R=C2H5, and x=2, denoted as DPS-4.
[0069] 2) Synthesis of (polyether) oligosiloxane (MPS-4) with one end blocked by a monosiloxy group
[0070] In a dry three-necked flask equipped with a thermometer, a reflux condenser and an electric stirrer, 0.01 mol (about 44.60 g) of a single-ended (hydroxy-terminated polyoxypropylene propyl) polymethylphenylsiloxane (CH3)3Si[OSiCH3(C6H5)] having a structure shown in formula (4) with m1=30, m2=0, R1'=CH3, R2'=ph, a1=0, b1=3, A'=-(OC3H6)3- was weighed in a molar ratio of about 1:3 between polyether polyorganosiloxane (PS-OH) containing C-OH at one end of the molecule and isocyanate silane (ICS). 30 OSi(CH3)2C3H6(OC3H6)3OH and 0.03 mol (about 6.16 g) 3-isocyanatepropyltrimethoxysilane (ICPTMS) were stirred and mixed, and the mixture was heated to 60°C and stirred for 6 hours. After the reaction was completed, 表=0.09MPa, the residual 3-isocyanatepropyltrimethoxysilane was evaporated under reduced pressure to obtain a colorless transparent liquid, which is a single-terminal (trimethoxysilylpropylcarbamate polyoxypropylenepropyl) polymethylphenylsiloxane having a structure as shown in formula (3) with m1=30, m2=0, R1'=CH3, R2'=ph, a1=0, b1=3, A'=-(OC3H6)3-, y=1, and R'=CH3, denoted as MPS-4, and used for later use.
[0071] (2) Preparation of polyether silicone composite material SMS-4
[0072] 64.0 g of α, ω-bis(methyldimethoxysilyl) end-capped polyether S230 (Shanghai Dongda Chemical Co., Ltd.) with a viscosity of about 10000 mPa.s, 28.0 g of α, ω-bis(methyldiethoxysilylpropylcarbamate polyoxypropylenepropyl) poly(dimethylsiloxane-co-methylphenylsiloxane) DPS-4, 8.0 g of single-ended (trimethoxysilylpropylcarbamate polyoxypropylenepropyl) polymethylphenylsiloxane MPS-4, 1.0 g of Clariant oil-soluble black color paste Colanyl Black N131-CN0030, 0.8 g of BYK-ATU dispersant, and 10.0 g of skin collagen powder were weighed in order by mass, and mixed evenly with a dispersing disk at a speed of 1000 r / min, and then 15.0 g of The 95% isopropanol-H2O solvent was stirred and dispersed for 40 minutes, and vacuum was used for degassing. Then, 0.5 g of bismuth diisooctanoate and 1.0 g of KH-550 catalyst were added, and stirred and mixed. The resulting slurry was a polyether silicone composite material, recorded as SMS-4.
[0073] (3) Preparation of polyether silicone synthetic leather PESiL-4
[0074] S1: The base fabric treated with base adhesive AE-1 is the same as that in Example 1.
[0075] S2: Take the polyether silicone combination material SMS-4, and use RDS-70 wire rod to evenly coat SMS-4 on the surface of the polyester microfiber base cloth treated with AE-1, and control the coating amount so that the coating thickness formed after the polyether silicone combination material is cured is about 218μm, and then paste a layer of fluorine texture release paper, and then cure at room temperature for 24h. After the surface is completely cured, remove the release paper, and then spray the newly exposed leather surface with a leather feel agent DC-Q2-3238-ethanol solution with a mass concentration of about 0.5%, and hang it in a drying room at 90℃ for 1h. The resulting leather sample is the polyether silicone synthetic leather PESiL-4.
[0076] Example 5
[0077] (1) Preparation of relevant raw materials
[0078] 1) Synthesis of bis(siloxy)-terminated urethane polyether polyorganosiloxane (DPS-5)
[0079] In a dry three-necked flask equipped with a thermometer, a reflux condenser and an electric stirrer, 0.02 mol (about 21.58 g) of α,ω-bis(hydroxyethyloxypropyl)-block polydimethylsiloxane HOC2H4OC3H6Si(CH3)2[OSi(CH3)2] having a structure shown in formula (2) with n1=10, n2=0, R1=R2=CH3, a=1, b=0 and A=-OC2H4- was weighed in a molar ratio of about 1:2 between polyether polyorganosiloxane (HO-PS-OH) containing C-OH at both ends of the molecule and isocyanate silane (ICS). 10 OSi(CH3)2C3H6OC2H4OH and 0.04 mol (about 8.21 g) 3-isocyanatepropyltrimethoxysilane (ICPTMS) were stirred and mixed, and the mixture was heated to 50°C and stirred continuously for 4.5 h. After the reaction was completed, 表 =0.09MPa, the residual 3-isocyanatepropyltrimethoxysilane was evaporated under reduced pressure to obtain a colorless transparent liquid, i.e., α,ω-bis(trimethoxysilylpropylcarbamate-ethylenoxypropyl)polydimethylsiloxane having a structure as shown in formula (1), wherein n1=10, n2=0, R1=R2=CH3, a=1, b=0, A=-OC2H4-, R=CH3, and x=1, denoted as DPS-5.
[0080] 2) Synthesis of single-end silaneoxy terminated urethane polyether polyorganosiloxane (MPS-5)
[0081] In a dry three-necked flask equipped with a thermometer, a reflux condenser and an electric stirrer, 0.01 mol (about 22.38 g) of a single-ended (hydroxy-terminated polyoxypropylene propyl) poly(dimethylsiloxane-co-methylphenylsiloxane) (CH3)3Si[OSi(CH3)2] having a structure shown in formula (4) with m1=25, m2=15, R1'=R2'=R3'=CH3, R4'=ph, a1=0, b1=6, A'=-(OC3H6)6- was weighed in a molar ratio of about 1:3 between polyether polyorganosiloxane (PS-OH) containing C-OH at one end of the molecule and isocyanate silane (ICS). 25 [OSiCH3(C6H5)] 15 OSi(CH3)2C3H6(OC3H6)6OH and 0.03 mol (5.68 g) 3-isocyanatepropylmethyldimethoxysilane (ICPMDMS) were stirred and mixed, and heated to 70°C and stirred for 4 hours. After the reaction was completed, 表=0.09MPa, the residual 3-isocyanatepropylmethyldimethoxysilane was evaporated under reduced pressure to obtain a colorless transparent liquid, which is a single-terminal (methyldimethoxysilylpropylcarbamate-based polyoxypropylenepropyl) poly(dimethylsiloxane-co-methylphenylsiloxane) with a structure as shown in formula (3), wherein m1=25, m2=15, R1'=R2'=R3'=CH3, R4'=ph, a1=0, b1=6, A'=-(OC3H6)6-, R=CH3, y=2, recorded as MPS-5, and used for later use.
[0082] (2) Preparation of polyether silicone composite material SMS-5
[0083] 64.0 g of α, ω-bis(methyldimethoxysilyl) end-capped polyether S230 (Shanghai Dongda Chemical Co., Ltd.) with a viscosity of about 11000 mPa.s, 30.0 g of α, ω-bis(trimethoxysilylpropylcarbamate ethylenoxypropyl) polydimethylsiloxane DPS-5, 7.5 g of single-ended (methyldimethoxysilylpropylcarbamate polyoxypropylenepropyl) poly(dimethylsiloxane-co-methylphenylsiloxane) MPS-5, 1.0 g of Clariant oil-soluble black color paste Colanyl Black N131-CN0030, 0.6 g of BYK-163 dispersant, and 12.0 g of skin collagen powder were weighed in parts by mass, stirred and mixed with a dispersing disk at a speed of 1000 r / min, and then 15.0 g of The 90% ethanol solvent was stirred and dispersed for 40 minutes, and vacuum was used for degassing. Then, 0.5 g of bismuth diisooctanoate and 1.0 g of KH-550 catalyst were added, and stirred and mixed. The resulting slurry was a polyether silicone composite material, which was recorded as SMS-5.
[0084] (3) Preparation of polyether silicone leather PESiL-5
[0085] S1: The base fabric treated with base adhesive AE-1 is the same as that in Example 1.
[0086] S2: Take the polyether silicone combination material SMS-5, and use RDS-70 wire rod to evenly coat SMS-5 on the surface of the polyester microfiber base cloth treated with AE-1, and control the coating amount so that the coating thickness formed after the polyether silicone combination material is cured is about 223μm, and then stick a layer of fluorine texture release paper, and then cure at room temperature for 24h. After the surface is completely cured, remove the release paper, and then spray the newly exposed leather surface with a leather feel agent DC-Q2-3238-ethanol solution with a mass concentration of about 0.5%, and hang it in a drying room at 90℃ for 1h. The resulting leather sample is the polyether silicone synthetic leather PESiL-5.
[0087] Example 6
[0088] The usage and dosage of raw materials were the same as those in Example 1, except that the mass of α,ω-bis(methyldimethoxysilyl) end-capped polyether S316 used in the preparation of the polyether silicone combination material in step (2) of Example 1 was replaced with polypropylene glycol with an average molecular weight of about 2000. The polyether silicone combination material and the polyether silicone leather were prepared in the same manner and used as Reference-1 of the present invention. The result: the product could not be cured.
[0089] Example 7
[0090] The usage and dosage of the raw materials are the same as those in Example 1, but the mass of α,ω-bis(trimethoxysilyl propyl carbamate polyoxypropylene propyl) block polymethylphenylsiloxane DPS-1 in step (2) of Example 1 is replaced with single-end (trimethoxysilyl propyl carbamate polyoxypropylene propyl) polydimethylsiloxane MPS-1, and the polyether silicone combination material and the polyether silicone leather are prepared in the same way, which is used as the reference-2 of the present invention. The result: it cannot be cured into a solid but is a viscous soft gel. It is speculated that this is because the polydimethylsiloxane segment has poor miscibility with the aliphatic system. When its dosage is too high, it will cause the system to be turbid and the reaction system cannot be effectively cured.
[0091] Example 8
[0092] The usage and dosage of the raw materials are the same as those in Example 1, except that the single-end (trimethoxysilyl propyl carbamate polyoxypropylene propyl) polydimethylsiloxane MPS-1 in step (2) of Example 1 is replaced with α,ω-bis (trimethoxysilyl propyl carbamate polyoxypropylene propyl) block polymethylphenylsiloxane DPS-1. The polyether silicone combination material and the polyether silicone leather are prepared in the same manner and used as Reference-3 of the present invention.
[0093] The polyether silicone leather samples prepared in Examples 1-8 and the reference were taken and balanced for 24 hours at room temperature 25±2°C and relative humidity RH of about 60%, and the performance test was performed:
[0094] Tensile strength and elongation at break: refer to GB / T528-2009 standard, and test with dumbbell-shaped type I specimen using universal testing machine. Leather surface hydrophobicity: expressed by the static contact angle (WCA) of water droplets on the surface of synthetic leather, using JC-2000C1 static contact angle measuring instrument, with a water droplet size of 5μL; Aging resistance (1000h×85℃×RH85%): refer to GB / T2423.24-1995 standard and measure with KK-SN-150 xenon lamp aging resistance test box; Friction fastness: test with friction force measuring instrument. In addition, other polyether composite materials are prepared as in Example 1 without adding DPS and MPS, and then synthetic leather is prepared, and the leather samples obtained are used as reference MS of the present invention. The performance test results of Examples 1-8 and reference MS are shown in Table 1.
[0095] Table 1 Performance test results of polyether silicone synthetic leather PESiL and reference
[0096]
[0097] ★: Good aging resistance, 1000h×85℃×RH85% without yellowing
[0098] As can be seen from Table 1, compared with the reference MS, the contact angles of the leather surfaces of the polyether silicone synthetic leather samples prepared in Examples 1-5 are all greater than 90°, indicating that the leather surface is hydrophobic and the hydrophobicity is significantly improved compared with the reference sample; in addition, compared with the reference MS, although the elongation at break of the PESiL-1 to PESiL-5 synthetic leather samples has decreased, it has generally reached 209% to 372%, indicating that the leather samples still have good elongation at break; in addition, the PESiL-1 to PESiL-5 leather samples are resistant to xenon lamp aging for 1000h at a temperature of 85°C and a relative humidity of RH of 85%, and there is no obvious yellowing on the leather surface, and the dry friction fastness of the tested leather samples generally reaches 3.5-4.5; this shows that the mechanical properties of the synthetic leather prepared in Examples 1-5 are good, and it is obvious that the introduction of phenyl polyether silicone has no significant effect on the mechanical properties of the finished leather.
Claims
1. A polyether silicone composite material, characterized in that: The composition comprises, by mass, 60-90 parts of α,ω-bissiloxy-terminated polyether MS, 5-30 parts of α,ω-bissiloxy-terminated polyorganosiloxane DPS, 5-10 parts of single-end siloxy-terminated polyorganosiloxane MPS, 1-10 parts of oil-soluble color paste, 0.5-1.0 parts of wetting and dispersing agent, 10-25 parts of skin collagen powder, 10-30 parts of alcohol-water solvent, and 0.2-0.5 parts of organic metal catalyst; The α,ω-disiloxy-terminated polyether MS is a polyether having a 2-3 functional siloxy group connected to each end of the molecule; The α,ω-disiloxy-terminated polyorganosiloxane DPS has a structure as shown in formula (I): In formula (I), n1, n2 = 0-40, n1 + n2 = 4-40, R = CH3 or C2H5, R1, R2, R3, R4 = CH3 or C6H5; A = -(OC2H4) a (OC3H6) b -, a=0-3, b=0-10, a+b=0-10; x=1-2; The single-end silaneoxy-terminated polyorganosiloxane MPS has a structure as shown in formula (II): In formula (II), m1, m2 = 0-40, m1 + m2 = 4-40, R' = CH3 or C2H5, R1', R2', R3', R4' = CH3 or C6H5; A' = -(OC2H4) a1 (OC3H6) b1 -, a1=0-3, b1=0-10, a1+b1=0-10; y=1-2.
2. The composite material according to claim 1, characterized in that: The α,ω-disiloxy-terminated polyorganosiloxane DPS is obtained by chemical reaction of a polyorganosiloxane HO-PS-OH containing hydroxyl groups at both ends of the molecule and isocyanate silane ICS. The molar ratio of the polyorganosiloxane HO-PS-OH containing hydroxyl groups at both ends of the molecule to the isocyanate silane ICS is 1:(2-5), the reaction temperature is 50-80°C, and the reaction time is 4-6h.
3. The composite material according to claim 2, characterized in that: The polyorganosiloxane HO-PS-OH containing hydroxyl groups at both ends of the molecule is one or more of α,ω-bis(hydroxypropyl) block polyorganosiloxane, α,ω-bis(hydroxyethyloxypropyl) block polyorganosiloxane, and bis(hydroxyl-terminated polyether) block polyorganosiloxane; The polyether group is a polyoxyethylene polyoxypropylene ether group; The polyorganosiloxane is one of polyorganosiloxanes whose main chain is polydimethylsiloxane, polydiphenylsiloxane, polymethylphenylsiloxane, poly(dimethylsiloxane-co-diphenylsiloxane) or poly(dimethylsiloxane-co-methylphenylsiloxane).
4. The composite material according to claim 1, characterized in that: The single-end silaneoxy-terminated polyorganosiloxane MPS is obtained by reacting a single-end hydroxyl-containing polyorganosiloxane PS-OH with an isocyanate silane ICS at a molar ratio of 1:(1-5) at 50-80° C. for 4-6 hours; the single-end hydroxyl-containing polyorganosiloxane PS-OH is selected from a single-end hydroxypropyl polyorganosiloxane, a single-end hydroxyl-terminated polyorganosiloxane polyoxyethylene polyoxypropylene propyl polyorganosiloxane.
5. The composite material according to any one of claims 2 to 4, characterized in that: The isocyanate silane ICS is one or more of 3-isocyanate propyl trimethoxy silane, 3-isocyanate propyl triethoxy silane, 3-isocyanate propyl methyl dimethoxy silane and 3-isocyanate propyl methyl diethoxy silane.
6. The composite material according to claim 1, characterized in that: The oil-soluble color paste is a dispersion formed by dispersing oil-soluble dyes or pigments in resin or solvent; The wetting and dispersing agent is one or more of BYK-ATU and BYK-163; The skin collagen powder is a powder obtained by recycling, decolorizing and crushing pig skin, cow skin and sheep skin; The alcohol-water solvent is an alcohol-water mixture in which 5%-10% of water is dissolved in a small molecule alcohol by mass fraction; the small molecule alcohol is one or more of ethanol, isopropanol, and tert-butanol; The organic metal catalyst is one or more of dibutyltin dilaurate, dibutyltin diacetate, bismuth diisooctanoate and zinc diisooctanoate.
7. The method for preparing synthetic leather using the combination of materials according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: fixing a substrate on a test bench, first coating a layer of aminosilane ring-opening modified epoxy resin bottom adhesive layer on the surface of the substrate; then stirring the polyether silicone composite material evenly, removing bubbles, evenly coating the composite material on the substrate surface after the bottom adhesive treatment, and curing at room temperature for 24-48 hours; and spraying a leather feel agent to obtain a polyether silicone synthetic leather.
8. The method according to claim 7, characterized in that The substrate is a non-woven fabric or ultra-fine fiber fabric made of polyester, nylon or polyurethane; the leather feel agent is DC-Q2-3238.
9. The method according to claim 7, characterized in that: The aminosilane ring-opening modified epoxy resin is obtained by reacting epoxy resin and aminosilane at a molar ratio of 1: (2-2.3) at 50-70° C. for 30-60 minutes; the epoxy resin is bisphenol A epoxy resin E51 or E44; the aminosilane is one or more of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldimethoxysilane, and 3-aminopropylmethyldiethoxysilane.
10. The polyether silicone synthetic leather obtained by the method according to any one of claims 7 to 9.
Citation Information
Patent Citations
Anti-adsorption, wear-resistant and scratch-resistant organic silicon leather and preparation method thereof
CN115595800A
Manufacturing process of environment-friendly organic silicon leather
CN115652651A
Preparation method of organic silicon leather coating
CN117487456A
Soft high-peel-strength moisture-permeable organic silicon leather and preparation method thereof
CN117779479A